Analysis of Consumer Behavior at Panorama Lembang Traditional Market West Bandung Regency - Dinihayati, Erti; Purwanti, Yanti (Jurnal Polisci, 2023)
The competition between businesses acting as producers of products and services is becoming a more prominent feature of today's economic development. One way for marketers to learn what their customers want and need is through retailing their products, and using intermediaries to distribute their products. Traditional markets offer many goods with varying grades and prices, making them good places to find retail trade. Many other retail businesses have recently emerged in various shapes and sizes. These include supermarkets and mini-marts maintained by both people and businesses and hypermarkets operated by foreign retailers. The survival of local markets, especially Panorama Market in Lembang District, West Bandung Regency, is threatened by the entry of foreign retailers into the domestic market. In this study, the "characteristics and behavior of consumers who shop at Lembang Panorama Market, West Bandung Regency" are to be ascertained and analyzed. The approach employed in this study is qualitative, used as a research technique that generates descriptive data from people who may be observed in the form of written or spoken words.